(3JGQjN GdNdaGAs - (3GdQHYj, GdbRhjfj, CHh YHO Gddg, GHf eGLg, eMeO Hf jRjO, J (B248 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3GdebUO GdKGfj aj GdLhGgQ hGdCYQGV haj aUhd ; GdChd aj GdLhGgQ bOe eHGMKgG eY eHGMK GdCYQGV dGf hLhg GdYQV eJhba Ydi hLhO GdLhgQ afGSH Pdc (B...s
(3BNQgG (B:s
... (3hNdY Ydjg ef GdNdGaI (B.. (3hcGfJ NdGaJg KdGK Sfjf hCMO YTQ TgQG (B.. (3GdeSJcaj HGddg CHh GdbGSe (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\144s
(3JWhQ cJGHI GdSjQI GdfHhjI , YeGQ YHhOi eMeO MSjf fUGQ (B273s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs